Altered Static and Dynamic Voxel-mirrored Homotopic Connectivity in Patients with Frontal Glioma. (10th May 2022) - Hu, Guanjie; Ge, Honglin; Yang, Kun; Liu, Dongming; Liu, Yong; Jiang, Zijuan; Hu, Xiao; Xiao, Chaoyong; Zou, Yuanjie; Liu, Hongyi; Hu, Xinhua; Chen, Jiu
Highlights: Glioma cause regional dysfunction and disturb long-distance functional connectivity, and the long-distance functional connectivity showed strong instability in patients with frontal glioma. The altered functional indicators may compensate for cognitive function in patients with frontal glioma. Long-distance functional protection may be more conducive for recovery of glioma patients. Abstract: Contralateral regions play critical role in functional compensation in glioma patients. Voxel-mirrored homotopic connectivity (VMHC) characterizes the intrinsic functional connectivity (FC) of the brain, considered to have a regional functional basis. We aimed to investigate the alterations of brain regional function and VMHC in patients with frontal glioma, and further investigated the correlation between these alterations and cognition. We enrolled patients with frontal glioma and matched healthy controls (HC). We chose degree centrality (DC), regional homogeneity (ReHo), and VMHC to investigate the alterations of regional function and intrinsic FC in patients. Furthermore, partial correlation analyses were conducted to explore the relationship between imaging functional indicators and cognitions. Compared with HC, patients showed decreased static VMHC within right and left middle frontal gyrus (MFG.R, MFG.L), left superior frontal gyrus (SFG.L), right precuneus (PCUN.R), and left precuneus (PCUN.L), decreased static DC within left cingulate gyrus (CG.L), right superior frontal gyrus (SFG.R), and right postcentral gyrus (POCG.R), decreased static ReHo within CG.L, decreased dynamic ReHo within right inferior parietal lobule (IPL.R), but increased dynamic VMHC (dVMHC) within PCUN.R and PCUN.L. Furthermore, values of decreased VMHC within MFG.R, decreased DC within CG.L, decreased ReHo within CG.L, and increased dVMHC within PCUN.R were significantly positively correlated with cognitive functions. We preliminarily confirmed glioma causes regional dysfunction and disturbs long-distance FC, and long-distance FC showed strong instability in patients with frontal glioma. Meanwhile, the correlation analyses indicated directions for cognitive protection in patients with frontal glioma.